Task-Based Language Teaching; Potential Benefits and Possible Criticisms in Indonesian Contexts - Maulana, Mochammad Ircham (Journal of English Teaching and Learning Issues, 2021)
The primary aim of English language teaching in Indonesia is to equip Indonesian students with communicative competence in English. However, due to the prevalent utilisation of traditional student-centered approaches that accentuates linguistic structural properties as well as the lack of exposure to and usage of the target language in the classroom, research has found that Indonesian school graduates’ English communicative skills are still low. Very few students can deliver ideas, thoughts, and feelings through English as a medium of communication. This conceptual review article aims to promote the viabilities of task-based language teaching (TBLT) method to accelerate students’ communicative skills in Indonesia. Drawing on a wide range of theories and research findings, it critically explores some potential benefits as well as addresses some possible criticisms of employing TBLT in Indonesia. It argues that TBLT promotes natural learning, generates students’ intrinsic motivation, and develops language skill development that can lead the students to accelerate their communicative competence.